Bilateral asymmetries assessment in elite and sub-elite male futsal players - López-Fernández, J.; Garcia-Unanue, J.; Sánchez-Sánchez, J.; Colino, E.; Hernando, E.; Gallardo, L. (International Journal of Environmental Research and Public Health, 2020)
This study aimed to investigate morphological, functional, and neuromuscular asymmetries on futsal players` lower limbs at different competitive levels. Sixteen male elite futsal players from the Spanish National Futsal League and thirteen male sub-elite futsal players from the third division participated in this study. Morphological asymmetry was assessed through bioelectrical impedance (fat-mass (g and %) and lean-mass (g)). Functional asymmetry was assessed by means of a 20-s static unipedal balance test. Finally, neuromuscular asymmetry was assessed using tensiomiography tests on both the rectus femoris (RF) and biceps femoris (BF) of each participant. The three tests conducted did not reveal significant bilateral asymmetries in elite players. On the other hand, sub-elite players showed significant bilateral asymmetry in fat-mass percentage between dominant and non-dominant limbs (+6%; CI95%: 1 to 11; ES: 0.88; p = 0.019). They also showed higher bilateral asymmetry in the delay time of the RF (+13%; CI95%: 7 to 21; ES: 1.3; p < 0.05). However, the static unipedal balance test (p > 0.05) did not evidence asymmetries regardless of the level of the participants. Elite futsal players do not develop bilateral asymmetries in lower limbs in the studied parameters. On the contrary, sub-elite players are likely to develop morphological and neuromuscular asymmetries between their dominant leg and non-dominant leg.